Synthesis and in vitro Experiment of Biomaterial Tricalcium Phosphate - X.V Bui (Universitas Gadjah Mada, 2016)
Calcium phosphate ceramics consist of materials such as hydroxyapatite, tricalcium phosphate (TCP), calcium phosphate cement (CPC), biphasic calcium phosphate, etc. CPCs have been used for filling bone defects in dentistry and orthopedics. Among these materials, ?-tricalcium phosphate is suggestedas an ideal candidate for bone graft in hard tissue engineering due to its high biocompatibility, bioactivity and bone bonding. The preparation, as well as the application of this powder material, has been the important topic of research in material science. In this paper, ?-tricalcium phosphate (?-TCP), a component that has chemical formulation similar to bone structure, was synthesized by the precipitate method and then calcinated at 1000oC for 5 h. The physico-chemical properties of synthetic material were examined by XRD, FT-IR and SEM methods. In vitro experience was also carried by soaking ?-TCP simulated body fluid powder in a different period of time. Obtained results confirmed the quality of ?-TCP synthetic material and its bioactivity.